Construction cash flow risk index - Hasan Mahmoud; Vian Ahmed; Salwa Beheiry (Journal of Risk and Financial Management, 2021)
As investment increases in capital projects, financial risks increase, and cash flow prediction and control become more paramount. Higher risks could hinder project performance and increase the chances of failure in multiple aspects of a project. While there are models that aim to assess and forecast risks in the construction industry, none present a technique to include the impact of risks on a project's cash flow. Therefore, cash flow forecasts tend to exceed the actual cash flow of a project due to inaccurate risk assessment. Thus, this paper presents the Cash Flow Risk Index (CFRI) development process quantifying the impact of risks on a project's cash flow from an owner's perspective. To that end, the study explored the literature to identify the risk factors that might impact a construction projects' cash flow and uncovered 44 factors. The study also validated and consolidated these factors to build a CFRI via a Delphi exercise, which reduced the factors from 44 to 36. In further iterations, the 36 factors were also shared with 32 construction industry professionals to rate their relative importance on a five-point Likert scale, from which relative importance index and weights were obtained. As a result, the CFRI was developed to measure the impact of different risk factors on a typical construction project's cash flow.
Keywords: 330; Cash Flow Risk Index; construction risks; Relative Importance Index